Penerapan Komunikasi TBAK (Tulis, Baca, Konfirmasi) dalam Penyampaian Informasi Kepada Mahasiswa AKPER Dharma Husada - Elfi Quyumi R; Erna Susilowati (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2019)
Nursing students are someone who is prepared to become a professional nurse in the future. Being a professional nurse must have a sense of responsibility or accountability wherever they carry out clinical practices including in high intensity rooms such as critical care rooms and emergency installations. Emergency Installation (ED). describe the implementation of TBaK communication (Write, Read, Confirm) in delivering information to Akper Dharma Husada students. This study uses a quantitative descriptive research approach. This research describes the application of TBaK communication (Write, Read, Confirm) in delivering information to Akper Dharma Husada students at the ED. This research was conducted at the IGD Gambiran Hospital in February 2019. The researcher used a questionnaire to collect data in this study. From the simple random sampling technique obtained 16 respondents. This study uses a descriptive approach. Based on the results of the research conducted in February 2019 at the IG of Gambiran Hospital, the communication results of 68.75% TB were enough. When communication between the giver and the recipient of the message goes well; then the information will be received in accordance with the intent of the giver of the message, the impact of the patient getting action in accordance with his treatment needs and the action will be well documented. TBaK communication is a new thing for students in the order of practice so it needs to be recommended for students and counselors to be disseminated and applied in any risky action to patients.